2007
DOI: 10.1002/ijc.22902
|View full text |Cite
|
Sign up to set email alerts
|

The tetraspanin CD9 inhibits the proliferation and tumorigenicity of human colon carcinoma cells

Abstract: The implication of the tetraspanin CD9 in cancer has received much recent attention and an inverse correlation between CD9 expression and the metastatic potential and cancer survival rate has been established for different tumor types. In contrast to the well-established role of CD9 in metastasis, very little is known about the involvement of this tetraspanin in the process of development of primary tumors. In the present study, we present evidence on the implication of CD9 in colon carcinoma tumorigenesis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 52 publications
6
73
0
Order By: Relevance
“…These results indicate that CD9 disruption could accelerate GSC differentiation. As CD9 has been demonstrated to regulate tumor cell viability, 26,27 we investigated the impact of CD9 on GSC proliferation and apoptosis, and found that CD9 disruption apparently inhibited GSC proliferation and significantly induced GSC apoptosis (Supplementary Figure S2h and Figure 1f). Collectively, these data demonstrate that CD9 is essential for maintaining the self-renewal and proliferation of GSCs.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that CD9 disruption could accelerate GSC differentiation. As CD9 has been demonstrated to regulate tumor cell viability, 26,27 we investigated the impact of CD9 on GSC proliferation and apoptosis, and found that CD9 disruption apparently inhibited GSC proliferation and significantly induced GSC apoptosis (Supplementary Figure S2h and Figure 1f). Collectively, these data demonstrate that CD9 is essential for maintaining the self-renewal and proliferation of GSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with studies on some cancer cells. Pretreatment of pre-B-cell acute lymphoblastic leukemia, 35 melanoma, 50 or colon carcinoma 51 with CD9 mAb enhanced their adhesion to fibronectin, endothelial, and bone marrow stromal cells, suggesting that CD9 is a negative regulator of cellular adhesion. Our observations, together with those in metastatic tumors, suggest that the presence of CD9 on CD34 ϩ cells might inhibit SDF-1-mediated cell motility to a certain extent, but that such activities could be modulated by adhesion to endothelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…ALB6 treatment of mice bearing CD9-expressing human gastric cancer cells has been recently shown to successfully inhibit tumor progression via not only antiproliferative and proapoptotic effects on malignant cells but also antiangiogenic effects on tumor vessels reducing microvessel density (42). Inhibitory effects of anti-CD9 mAb on in vivo tumorigenicity as well as in vitro proliferation of human colon carcinoma cells has also been reported (43). Regulation of tumor angiogenesis by ALB6 in vivo is likely and acceptable because another anti-CD9 mAb (ALMA.1) inhibited human vascular endothelial cell migration toward ECM proteins at wound lesion and impaired its repair (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antibody-dependent cellular cytotoxicity might have participated in antitumor activity by anti-CD9 antibodies in vivo (42,43), although the authors did not refer to the matter. IgG 1 subclass antibodies such as trastuzumab, rituximab, and cetuximab are well known to preferentially induce this immune reaction because they have longer half-lives and could bind to all subtypes of FcγR on effector cells (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%